Analisis Pendapatan Usaha Stic Rumput Laut Pada Industri Rumah Tangga Kub Kembang Baru Nangahure Kecamatan Alok Barat Kabupaten Sikka - Odilia Ketuko Witin; Taras Iawan Saputera Wanda (Peneliti.net, 2022)
Seaweed is one type of cultivation that has the opportunity to be developed. This seaweed stick business is one of the right alternatives to be developed in sikka regency. The purpose of this study wants to find out how much seaweed stick business income in KUB Kembang Baru Nangahure and also to find out whether the seaweed stick business is worth trying to do. The data used in the research is primary data and secondary data. As for the results of calculations from the analysis of seaweed stick business income in the KUB Kembang Baru household industry, conclusions were obtained. The total cost of receipts obtained by KUB Kembang Baru is Rp 3,750,000 then the total production costs incurred amounted to 2,928,000, so that the total revenue is reduced by the total cost after processing the income obtained by the KUB Kembang Baru Nangahure household industry which produces seaweed sticks of Rp 822,000. Seaweed stick business in the household industry KUB Kembang Baru Nangahure seen from revenue cost this business ratio is worth trying. Because the value of R / C is greater than one which is 1.28 Rupiah.